Baicalin mitigates hyperglycemia-linked intestinal epithelial barrier impairment in part by inhibiting the formation of neutrophil extracellular traps - Cai, Yiqing; Yang, Qinbo; Tang, Xinmiao; Wang, Peiwei; Cui, Jingang; Du, Xiaoye; Zhang, Teng; Chen, Yu (Frontiers in Immunology, 2025)
BackgroundUnder hyperglycemic conditions, impaired intestinal barrier integrity leads to heightened level of inflammation, playing important roles in driving diabetic complications. Emerging evidence supports the implications of neutrophil extracellular traps (NETs) in the pathogenesis of diabetes. However, whether NETs contribute to hyperglycemia-linked intestinal barrier impairment remains to be investigated. Moreover, baicalin, the major chemical component of Scutellaria baicalensis Georgi, is equipped with twofold intestinal protective and neutrophil suppressive activities. Yet, it is unclear if baicalin is effective at mitigating hyperglycemia-linked NETs-mediated intestinal barrier impairment.MethodsTo directly address the mechanistic implications of NETs in hyperglycemia-linked intestinal epithelial barrier impairment, the impact of DNase I treatment or Padi4 gene deficiency on intestinal epithelial integrity was first examined in the streptozotocin (STZ)-induced hyperglycemic mice in vivo. Next, the pharmacological impact of baicalin on NETs formation and intestinal epithelial barrier impairment was investigated in high glucose- and/or lipopolysaccharides (LPS)-stimulated neutrophils in vitro and in STZ-induced hyperglycemic mice in vivo, respectively.ResultsThe in vitro experiments confirmed that high glucose and/or LPS induced NETs formation. NETs directly impaired the viability and tight junction of the intestinal epithelial cells. The histological and immunohistochemical examinations unveiled that along with impaired intestinal epithelial morphology, citrullinated histone H3 (H3Cit), a marker of NETs, and neutrophil specific Ly6G were readily detected in the intestinal epithelium in the hyperglycemic mice. Without affecting the presence of neutrophils, DNase I treatment or Padi4 gene deficiency markedly mitigated intestinal NETs formation and improved the intestinal morphology in the hyperglycemic mice. Notably, baicalin suppressed NETs formation and inhibited histone H3 citrullination stimulated by high glucose, LPS or both in vitro. Furthermore, baicalin blunted NETs formation and partially preserved the integrity of the intestinal epithelium in the hyperglycemic mice in vivo.ConclusionsThe current study sheds new light on the pathophysiological implications of NETs in intestinal epithelial barrier impairment under hyperglycemic conditions. Most importantly, the findings here demonstrate for the first time that baicalin directly inhibits NETs formation stimulated by high glucose and/or LPS, which may in part account for its pharmacological effects at protecting against hyperglycemia-linked intestinal epithelial barrier impairment.